Plasma progesterone, estradiol, and unconjugated estriol concentrations in twin pregnancies: Relation with cervical length and preterm delivery. (21st October 2018) - Johnsson, Vilma L.; Pedersen, Nina G.; Worda, Katharina; Krampl‐Bettelheim, Elisabeth; Skibsted, Lillian; Hinterberger, Stefan; Strobl, Isolde; Bowman, Maria E.; Smith, Roger; Tabor, Ann; Rode, Line
Abstract: Introduction: The aim of this study was to examine the association between plasma hormone concentrations, cervical length, and preterm delivery in twin pregnancies, including the effect of progesterone treatment. Material and methods: This study included 191 women pregnant with twins from a randomized placebo‐controlled trial. A baseline blood sample was collected at 18‐24 weeks before treatment with vaginal progesterone (n = 95) or placebo pessaries (n = 96), and 167 (87.4%) women had a second sample collected after 4‐8 weeks of treatment. At baseline, 155 (81.2%) women had their cervical length measured. Progesterone, estradiol, and unconjugated estriol concentration was measured, and the association between hormone concentrations, cervical length, and gestational age at delivery was examined. Hormone concentrations were compared in the placebo and progesterone group. Statistical analysis included Spearman's rho, Mann‐Whitney U test, Cuzick's test for trends, and linear regression analyses. Results: A short cervical length was associated with preterm delivery. Cervical length and hormone concentrations were not associated (Spearman's rho; progesterone −.05, estradiol .04, estriol .08). Decreasing gestational age at delivery was associated with higher progesterone and estradiol concentrations at baseline ( P trend; progesterone 0.04, estradiol 0.02) but not in the second sample or in the weekly change between samples. Progesterone treatment did not increase the progesterone concentration. Conclusions: Plasma concentrations of progesterone, estradiol, and unconjugated estriol at 18‐24 weeks are not associated with cervical length or preterm delivery in twin pregnancies. Vaginal progesterone treatment does not increase the circulating progesterone concentration in twin pregnancies. Cervical length, but not hormone concentration, is predictive of preterm delivery in twin gestations.